"Desarrollo de una aplicación web para venta de servicios de transportación terrestre bajo el modelo de negocio de tarjeta prepago" - Guerrero Pazmiño, Shirley Silvana (2013)
At present a large part of the population has access to technological devices that support their work activities, these technologies contribute significantly to the development of new models of appropriate business development companies. This research tries to use the Information Technologies and Communication ICT to contribute to a new business model in the interprovincial transportation. In trying to implement a new business model aims to solve the problems of users to make ticket purchases holiday season especially, because they will not have the need for long queues to purchase, in the same way solve problems booking tickets, sending parcels, among others. To output all these problems arises the idea of a web application for sale of land transportation services under the business model prepaid card, thus allowing control of the primary activities of the Cooperative. The web system has processes: selling prepaid cards, ticket sales through these cards, management plan routes and schedules, reservations, parcel tracking, reporting, among other features. The importance of this research lies mainly in the fact implement a new business model based on the prepaid card and implemented by the Information Technology and Communication and getting businesses have land transport options accessible with new business from the Internet to expand its customer base leveraging the new culture that web users have